Plant mitochondrial introns as genetic markers - conservation and variation - Grosser, Melinda R.; Sites, Samantha K.; Murata, Mayara M.; Lopez, Yolanda; Chamusco, Karen C.; Love Harriage, Kyra; Grosser, Jude W.; Graham, James H.; Gmitter, Fred G.; Chase, Christine D. (Frontiers in Plant Science, 2023)
Plant genomes are comprised of nuclear, plastid and mitochondrial components characterized by different patterns of inheritance and evolution. Genetic markers from the three genomes provide complementary tools for investigations of inheritance, genetic relationships and phenotypic contributions. Plant mitochondrial genomes are challenging for universal marker development because they are highly variable in terms of size, gene order and intergenic sequences and highly conserved with respect to protein-coding sequences. PCR amplification of introns with primers that anneal to conserved, flanking exons is effective for the development of polymorphic nuclear genome markers. The potential for plant mitochondrial intron polymorphisms to distinguish between congeneric species or intraspecific varieties has not been systematically investigated and is possibly constrained by requirements for intron secondary structure and interactions with co-evolved organelle intron splicing factors. To explore the potential for broadly applicable plant mitochondrial intron markers, PCR primer sets based upon conserved sequences flanking 11 introns common to seven angiosperm species were tested across a range of plant orders. PCR-amplified introns were screened for indel polymorphisms among a group of cross-compatible Citrus species and relatives; two Raphanus sativus mitotypes; representatives of the two Phaseolus vulgaris gene pools; and congeneric pairs of Cynodon, Cenchrus, Solanum, and Vaccinium species. All introns were successfully amplified from each plant entry. Length polymorphisms distinguishable by gel electrophoresis were common among genera but infrequent within genera. Sequencing of three introns amplified from 16 entries identified additional short indel polymorphisms and nucleotide substitutions that separated Citrus, Cynodon, Cenchrus and Vaccinium congeners, but failed to distinguish Solanum congeners or representatives of the Phaseolus vulgaris major gene pools. The ability of primer sets to amplify a wider range of plant species' introns and the presence of intron polymorphisms that distinguish congeners was confirmed by in silico analysis. While mitochondrial intron variation is limited in comparison to nuclear introns, these exon-based primer sets provide robust tools for the amplification of mitochondrial introns across a wide range of plant species wherein useful polymorphisms can be identified.